2001
DOI: 10.3171/jns.2001.94.6.0880
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of intracranial aneurysms by using Guglielmi detachable coils in awake patients: safety and feasibility

Abstract: Embolization of intracranial aneurysms performed using GDCs in the awake patient appears to be safe and feasible and allows intraprocedural evaluation of the patient. Potential advantages, including decreased cardiopulmonary morbidity rates, shorter hospital stay, and lower hospital costs, still require confirmation by a direct comparison with other anesthetic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 24 publications
1
66
0
Order By: Relevance
“…18,19 However, many studies have suggested that the rate of emergent endotracheal intubation among patients with conscious sedation receiving neuroendovascular therapies is very low. 17,[20][21][22] The findings of this meta-analysis that conscious sedation was actually associated with higher rates of recanalization and no increase in intraprocedural complications should assuage concerns about the perceived disadvantages of conscious sedation for the interventionalist. In contrast to general anesthesia, conscious sedation allows intraprocedural monitoring of neurologic deficits, allowing operators to adjust the treatment strategy if needed.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, many studies have suggested that the rate of emergent endotracheal intubation among patients with conscious sedation receiving neuroendovascular therapies is very low. 17,[20][21][22] The findings of this meta-analysis that conscious sedation was actually associated with higher rates of recanalization and no increase in intraprocedural complications should assuage concerns about the perceived disadvantages of conscious sedation for the interventionalist. In contrast to general anesthesia, conscious sedation allows intraprocedural monitoring of neurologic deficits, allowing operators to adjust the treatment strategy if needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the procedural costs of anesthetic agents, anesthesia personnel, and mechanical ventilation, considerable expenses can be avoided with reduction of hospital and ICU stays. At some institutions, general anesthesia for a 3-hour embolization procedure may cost $1350 7 ; the avoidance this fee reduced mean total hospital cost at 1 institution by 41%. 18 Even so, a technically successful procedure (ie, revascularization after ischemic stroke or technically successful aneurysm embolization) does not necessarily correlate with good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] According to a study by Jumaa et al, 8 2 patients (2.7%) were emergently intubated because of conscious sedation failure among 73 patients with acute ischemic stroke treated endovascularly with conscious sedation. In elective carotid stent placements, Chamczuk et al 9 found that only 2 of 63 (3%) patients had to be converted to general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Our center usually uses local rather than general anesthesia, in contrast to most centers, 9,35,45) to assess the neurological status during the procedure, detect thromboembolic complications early, and minimize neurological complications. 32) General anesthesia was used if…”
Section: Patient Populationmentioning
confidence: 99%